C-REACTIVE PROTEIN LEVEL IN CORONARY ARTERY DISEASE AND ITS CORRELATION WITH SERUM D-DIMER - Gul, Chaman; Marwat, Zahid Irfan; Israr, Mohammad; Hanif, Ruhila; Arshad, Muhammad (Journal of Ayub Medical College Abbottabad, 2016)
Background: C-reactive protein concentration has continuous associations with risk of coronary artery disease, ischemic stroke and death from several cancers. In addition, several studies have shown that CRP could be used to predict first ever myocardial infarction and stroke in healthy subjects, as well as outcome in acute setting. High levels of another biomarker, D-dimer, have been found to be independently associated with occurrence of coronary events. Methods: This correlational study was carried out at the Department of Cardiology, Ayub Teaching Hospital Abbottabad, in collaboration with the department of Biochemistry Postgraduate Medical Institute Lahore from 15th July 2013 to 15th May 2014. Patients aged 30 years or more of either gender having coronary artery disease was included in the study. Their serum D-dimer levels and C-reactive protein levels were measured for correlation with coronary artery disease. Results: A total of 50 patients of CAD were included in this study. Out of these 30 (60%) were males and 20 (40%) were females. Elevated CRP levels and D-dimer levels were noted in all of these patients. Pearson correlation coefficient test was performed on both CRP and D-dimer levels. Pearson correlation coefficient was calculated to be r= -0.1522 and when a p value was calculated, it was found to be 0.292 which implied that the results were not significant. Conclusion: This study showed that there is no correlation between CRP levels and D-dimer levels in patients with Coronary Artery Disease. Keywords: CRP; Coronary Artery Disease; Hypertension; Smoking; Family history; Diabetes Mellitus; D-dimers